Region- and layer-specific investigations of the human menisci using SHG imaging and biaxial testing - Rasheed, Bismi; Ayyalasomayajula, Venkat; Schaarschmidt, Ute; Vagstad, Terje; Schaathun, Hans Georg (Frontiers in Bioengineering and Biotechnology, 2023)
In this paper, we examine the region- and layer-specific collagen fiber morphology via second harmonic generation (SHG) in combination with planar biaxial tension testing to suggest a structure-based constitutive model for the human meniscal tissue. Five lateral and four medial menisci were utilized, with samples excised across the thickness from the anterior, mid-body, and posterior regions of each meniscus. An optical clearing protocol enhanced the scan depth. SHG imaging revealed that the top samples consisted of randomly oriented fibers with a mean fiber orientation of 43.3o. The bottom samples were dominated by circumferentially organized fibers, with a mean orientation of 9.5o. Biaxial testing revealed a clear anisotropic response, with the circumferential direction being stiffer than the radial direction. The bottom samples from the anterior region of the medial menisci exhibited higher circumferential elastic modulus with a mean value of 21 MPa. The data from the two testing protocols were combined to characterize the tissue with an anisotropic hyperelastic material model based on the generalized structure tensor approach. The model showed good agreement in representing the material anisotropy with a mean r2 = 0.92.